SOCIOLINGUISTIC ASPECTS OF ENGLISH AS A GLOBAL LANGUAGE - Jovliyeva Nafosat Bahodir qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Annotation: This article discusses the sociolinguistic dimensions of English as a global language and explores how social, cultural, and political factors influence its worldwide spread and usage. The paper highlights the roles of English in international communication, education, media, and technology, emphasizing the relationship between language, identity, and power. The study also examines varieties of English that have emerged due to globalization and language contact, such as World Englishes, and considers both the advantages and challenges of English dominance in global communication. The findings suggest that English functions not only as a linguistic tool but also as a social phenomenon that shapes intercultural relations and linguistic diversity in the modern world.